2019
DOI: 10.1155/2019/2603730
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Leishmaniasis: The Complexity of Host’s Effective Immune Response against a Polymorphic Parasitic Disease

Abstract: This review is aimed at providing a comprehensive outline of the immune response displayed against cutaneous leishmaniasis (CL), the more common zoonotic infection caused by protozoan parasites of the genus Leishmania. Although of polymorphic clinical presentation, classically CL is characterized by leishmaniotic lesions on the face and extremities of the patients, which can be ulcerative, and even after healing can lead to permanent injuries and disfigurement, affecting significantly their psychological, soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
60
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 114 publications
(206 reference statements)
0
60
0
4
Order By: Relevance
“…Immunity against Leishmania is complex and depends on many factors, such as genetic diversity, parasite species and isolates (27)(28)(29). Leishmania spp.…”
Section: An Overview On Anti-leishmania Immunitymentioning
confidence: 99%
“…Immunity against Leishmania is complex and depends on many factors, such as genetic diversity, parasite species and isolates (27)(28)(29). Leishmania spp.…”
Section: An Overview On Anti-leishmania Immunitymentioning
confidence: 99%
“…There are still many gaps in the knowledge of how a protective CD4 + T cell response against Leishmania is activated, maintained, and controlled (26). In the last years it has been demonstrated that the expression of co-inhibitory receptors on activated T cells during the course of an immune response plays a pivotal role in dampening T cell activity (27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of multiple Leishmania species with overlapping clinical features that sometimes leads to misdiagnosis in endemic areas [ 7 ], as well as the genetic heterogeneity of the parasite [ 8 , 9 ], accentuate requirement for development of laboratory tests with high accuracy to be used for species identification of Leishmania spp. [ 10 ]. However, conventional parasitology methods have an intermediate diagnostic sensitivity on dermal aspirate samples of CL, as they are influenced by the sampling procedure, type of skin lesion, parasite load and technical personnel expertise [ 11 ].…”
Section: Introductionmentioning
confidence: 99%